High-entropy silicate microwave dielectric material for realizing temperature stability based on oxygen octahedron distortion regulation and preparation method of high-entropy silicate microwave dielectric material
By regulating oxygen octahedral distortion with a high entropy meter, a high entropy silicate microwave dielectric material with a value of nearly zero was prepared, which solved the problem of poor meter meter meter meter in the existing silicate materials, improved the stability of microwave components, and was suitable for the new generation of wireless mobile communications and microwave communications.
Patent Information
- Application Number
- CN202411833882.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The resonant frequency temperature coefficient (τf) value of existing silicate microwave dielectric materials is poor, which limits its application in microwave components.
Through the high entropy strategy, a high-entropy silicate microwave dielectric material composed of chemically composed of Li(Yb0.2Ho0.2Tm0.2In0.2Y0.2)SiO4 was prepared, with a sintering temperature of 1060-1140℃ to achieve a near-zero τf value.
The τf value of high-entropy silicate microwave dielectric material is achieved close to zero, which improves the stability of microwave components and is suitable for the new generation of wireless mobile communication and microwave communication.
Smart Images

Figure CN119551975A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of microwave electronic ceramic materials, and in particular to a high entropy silicate microwave dielectric material that achieves temperature stability based on oxygen octahedron distortion regulation and a preparation method thereof. Background Art
[0002] With the innovation of the new generation of wireless communication network technology, higher requirements are put forward for the miniaturization and high stability of microwave components. Due to the main characteristics of low latency (time delay), large bandwidth and high-speed data transmission of 5G technology, it has a low dielectric constant (ε r ) and new microwave dielectric materials with high quality factor (Q×f) need to be further explored. More importantly, the resonant frequency temperature coefficient (τ f ) is essential to ensure the operation stability of the equipment. Silicates are known for their high Q×f value and low ε r Most silicates have a τ value due to structural problems. f The value is relatively poor, which greatly limits the application of silicates in practice. Taking Mg2SiO4 with olivine structure as an example, the Q×f value of Mg2SiO4 can be as high as 240000GHz, while its poor τ f The value (-67ppm / ℃) has greatly limited its practical application. Therefore, how to improve the τ of silicate f Value is an urgent problem to be solved.
[0003] In 2004, Yeh et al. proposed the concept of high entropy alloys, which have many new advantages over traditional alloys. As high entropy alloy technology matures, the concept of high entropy has gradually been applied to other fields, such as high entropy ceramics. In 2015, Rost et al. prepared high entropy rock salt oxide ceramics and successfully applied high entropy to the field of ceramics. High entropy has a good improvement on the performance of ceramics in all aspects. Therefore, how to use high entropy to improve the τ of silicates? f It is worth people's exploration.
[0004] For materials with olivine structure, τ f The value is usually affected by the presence of oxygen octahedrons in the structure. In recent years, more and more studies have used high entropy to regulate the distortion of oxygen octahedrons to improve τ. f For example, Liu et al. prepared high entropy silicates (Mg 0.2 Ni 0.2 Zn 0.2 Co 0.2 Mn 0.2 )2SiO4, its τ f The value is -38.2ppm / ℃, and the oxygen octahedral distortion is 1.8×10-3 , which improves the τ of Mg2SiO4 to a certain extent f value. But its τ f There is still much room for improvement. Summary of the invention
[0005] One of the purposes of the present invention is to provide a high entropy silicate microwave dielectric material that achieves temperature stability based on the regulation of oxygen octahedral distortion to solve the above-mentioned problems.
[0006] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: a high entropy silicate microwave dielectric material based on oxygen octahedral distortion regulation to achieve temperature stability, the chemical composition of the material is: Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 )SiO4, the sintering temperature during preparation is 1060~1140℃.
[0007] As a preferred technical solution, the sintering temperature during preparation is 1060-1100°C.
[0008] The present invention improves its τ by regulating the oxygen octahedral distortion f The smaller the oxygen octahedral distortion, the smaller the τ f The closer the value is to zero.
[0009] The second object of the present invention is to provide a method for preparing the high entropy silicate microwave dielectric material based on the above-mentioned regulation of oxygen octahedral distortion to achieve temperature stability, comprising the following steps:
[0010] (1) Using Yb2O3, Ho2O3, Tm2O3, In2O3, Y2O3 and Li2CO3 as raw materials, according to Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 ) SiO4 stoichiometric ratio is weighed, and then the weighed raw materials are mixed and ball milled once, and the materials are dried to obtain a dried material;
[0011] (2) The dried material obtained in step (1) is placed in an alumina crucible and compacted, and the temperature is raised to 1000° C. at a rate of 3 to 6° C. / min, and then kept at this temperature for 2 to 6 hours, and then cooled to room temperature with the furnace to obtain Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 )SiO4 calcined material;
[0012] (3) Li(Yb) obtained in step (2) 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 ) SiO4 pre-sintered material is placed in a ball mill, and subjected to secondary ball milling and mixing to obtain a slurry;
[0013] (4) drying the slurry obtained in step (3) to constant weight, then granulating it and pressing it into a sample;
[0014] (5) placing the sample obtained in step (4) in a high-temperature sintering furnace, heating the temperature to 400-600° C. at a heating rate of 3-6° C. / min and keeping the temperature for 2-6 h, and finally cooling the sample to room temperature in the furnace to obtain a debinding green sample;
[0015] (6) placing the green sample obtained in step (5) in a high-temperature sintering furnace, heating the temperature to 1060-1140° C. at a heating rate of 3-6° C. / min, and keeping the temperature for 2-6 h, and finally cooling the furnace to room temperature to obtain a high entropy silicate microwave dielectric material with a resonant frequency temperature coefficient of near zero.
[0016] As a preferred technical solution, in step (1) and step (3), zirconium oxide balls are used as grinding balls and deionized water is used as ball milling medium.
[0017] As a preferred technical solution, in step (4), 20 wt % PVA solution is added as a binder during granulation.
[0018] As a preferred technical solution, in step (4), the pressing pressure is 20 MPa, and the size of the pressed cylindrical sample is: diameter 12 mm×thickness 4-6 mm.
[0019] The microwave dielectric material of the present invention mainly contains LiTmSiO4 and LiY9(SiO4)6O2 as the phase components, and is obtained by solid phase reaction method with near zero τ f The microwave dielectric material presented by the present invention has a near-zero τ f value (-1.28ppm / ℃).
[0020] Compared with the prior art, the advantages of the present invention are: f = +23.3ppm / ℃) and improves on it by controlling the oxygen octahedral distortion through a high entropy strategy so that the whole system has a near-zero τ f value, and does not cause significant deterioration in other microwave dielectric properties and sintering temperature. The near-zero τ provided by the present invention f Microwave dielectric materials: Li(Yb 0.2 Ho 0.2 Tm0.2 In 0.2 Y 0.2 )SiO4, the sintering temperature is 1060~1140℃, τ f =-1.28ppm / ℃,ε r =9.1~9.8, Q×f=15 700~20 100GHz; τ near zero f The value can improve the stability of the manufactured microwave components and can be widely used in the new generation of wireless mobile communications and microwave communications. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 X-ray diffraction (XRD) patterns of samples sintered at 1060-1140°C;
[0022] Figure 2 The microwave dielectric properties of the samples sintered at 1060-1140°C are shown;
[0023] Figure 3 Li(Yb) of Comparative Example 1 0.25 Ho 0.25 Tm 0.25 Y 0.25 ) X-ray diffraction (XRD) pattern of SiO4 sintered at 1040-1080°C;
[0024] Figure 4 Li(Yb) of Comparative Example 1 0.25 Ho 0.25 Tm 0.25 Y 0.25 )Microwave dielectric properties of SiO4 sintered at 1040-1080℃. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with embodiments.
[0026] Embodiment 1:
[0027] A high entropy silicate microwave dielectric material that regulates oxygen octahedron distortion based on high entropy effect to make the resonant frequency temperature coefficient close to zero, and the specific preparation method thereof is as follows:
[0028] Step 1: According to Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2) The raw materials are weighed and prepared according to the stoichiometric ratio of SiO4; the prepared raw materials are placed in a ball mill jar containing zirconium balls, deionized water is used as the ball milling medium, the ball mill speed is set to 250rpm, the ball milling time is set to 4h, and after the ball milling is completed, the slurry is placed in a constant temperature drying oven and dried to constant weight for standby use;
[0029] Step 2: The powders agglomerated after drying in step 1 were crushed in a mortar, put into a crucible for compaction, and heated to 100°C at a rate of 5°C / min, then heated to 1000°C at a rate of 10°C / min for pre-sintering, and then kept at this temperature for 4 hours, and then cooled to 500°C at a rate of 5°C / min and cooled to room temperature with the furnace to obtain Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 ) SiO4 pre-sintered material, and then putting the pre-sintered material into a ball mill for secondary ball milling and mixing;
[0030] Step 3: Add 20 wt% PVA solution as a binder to the powder obtained in step 2, granulate, and uniaxially dry press into a cylinder of 12 mm (diameter) × 6 mm (thickness) at 20 MPa;
[0031] Step 4: Place the green sample obtained in step 3 into a high-temperature sintering furnace, heat it to 100°C at a heating rate of 5°C / min, then heat it to 600°C at a heating rate of 10°C / min and keep it at that temperature for 4h, finally cool it to 500°C at a heating rate of 5°C / min and then cool it to room temperature with the furnace to obtain a green sample after debinding;
[0032] Step 5: Place the green sample after debinding in step 4 into the high-temperature sintering furnace again, and heat it to 100°C at a heating rate of 5°C / min, then to 1000°C at a heating rate of 10°C / min, and then to 1060°C at a heating rate of 5°C / min for sintering, and keep it warm for 4h. After the end of the heat preservation, reduce the temperature to 500°C at a rate of 5°C / min and then cool it to room temperature with the furnace to obtain a near-zero τ f High entropy silicate microwave dielectric materials with high values;
[0033] Figure 1 XRD patterns of samples at different sintering temperatures. Figure 1 It can be seen that the sample contains LiTmSiO4 and LiY9(SiO4)6O2 phases when the sintering temperature is 1060℃;
[0034] Li(Yb) at different sintering temperatures 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 )SiO4 microwave dielectric properties such as Figure 2 As shown in the figure, when the sintering temperature is 1060℃, τ f =-1.28ppm / ℃, Q×f=20 100GHz, ε r =9.4, oxygen octahedron distortion is 2.50×10 -4 .
[0035] Embodiment 2:
[0036] A high entropy silicate microwave dielectric material that regulates oxygen octahedron distortion based on high entropy effect to make the resonant frequency temperature coefficient close to zero, and the specific preparation method thereof is as follows:
[0037] Step 1: According to Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 ) The raw materials are weighed and prepared according to the stoichiometric ratio of SiO4; the prepared raw materials are placed in a ball mill jar containing zirconium balls, deionized water is used as the ball milling medium, the ball mill speed is set to 250rpm, the ball milling time is set to 4h, and after the ball milling is completed, the slurry is placed in a constant temperature drying oven and dried to constant weight for standby use;
[0038] Step 2: The powders agglomerated after drying in step 1 were crushed in a mortar, put into a crucible for compaction, and heated to 100°C at a rate of 5°C / min, then heated to 1000°C at a rate of 10°C / min for pre-sintering, and then kept at this temperature for 4 hours, and then cooled to 500°C at a rate of 5°C / min and cooled to room temperature with the furnace to obtain Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 ) SiO4 pre-sintered material, and then putting the pre-sintered material into a ball mill for secondary ball milling and mixing;
[0039] Step 3: Add 20 wt% PVA solution as a binder to the powder obtained in step 2, grind and granulate, and uniaxially dry press into a cylinder of 12 mm (diameter) × 6 mm (thickness) at 20 MPa;
[0040] Step 4: Place the green sample obtained in step 3 into a high-temperature sintering furnace, heat it to 100°C at a heating rate of 5°C / min, then heat it to 600°C at a heating rate of 10°C / min and keep it at that temperature for 4h, finally cool it to 500°C at a heating rate of 5°C / min and then cool it to room temperature with the furnace to obtain a green sample after debinding;
[0041] Step 5: Place the green sample after debinding in step 4 into the high-temperature sintering furnace again, and heat it to 100°C at a heating rate of 5°C / min, then to 1000°C at a heating rate of 10°C / min, and then to 1100°C at a heating rate of 5°C / min for sintering, and keep it warm for 4 hours. After the end of the heat preservation, reduce the temperature to 500°C at a rate of 5°C / min and then cool it to room temperature with the furnace to obtain a near-zero τ f High entropy silicate microwave dielectric materials;
[0042] The phase composition of the sample sintered at 1100℃ is as follows Figure 1 As shown in the figure, it can be seen that the phase composition of the sample at this time is LiTmSiO4 phase and LiY9(SiO4)6O2 phase. Figure 2 It can be seen from the microwave dielectric properties of the sample at 1100℃, τ f =+1.26ppm / ℃,Q×f=18 300GHz,ε r =9.8, oxygen octahedron distortion is 2.45×10 -4 .
[0043] Comparative Example 1:
[0044] In order to illustrate that the present invention is based on the high entropy effect, τ f The value is close to zero, not due to the multiphase composite effect, the microwave dielectric material Li (Yb 0.25 Ho 0.25 Tm 0.25 Y 0.25 ) The specific preparation method, properties and phase composition of SiO4 are described as follows:
[0045] Step 1: According to Li(Yb 0.25 Ho 0.25 Tm 0.25 Y 0.25 ) The raw materials are weighed and prepared according to the stoichiometric ratio of SiO4; the prepared raw materials are placed in a ball mill jar containing zirconium balls, deionized water is used as the ball milling medium, the ball mill speed is set to 250rpm, the ball milling time is set to 4h, and after the ball milling is completed, the slurry is placed in a constant temperature drying oven and dried to constant weight for standby use;
[0046] Step 2: The powders agglomerated after drying in step 1 were crushed in a mortar, put into a crucible for compaction, and heated to 100°C at a rate of 5°C / min, then heated to 1000°C at a rate of 10°C / min for pre-sintering, and then kept at this temperature for 4 hours, and then cooled to 500°C at a rate of 5°C / min and cooled to room temperature with the furnace to obtain Li(Yb 0.25 Ho 0.25 Tm 0.25 Y 0.25) SiO4 pre-sintered material, and then putting the pre-sintered material into a ball mill for secondary ball milling and mixing;
[0047] Step 3: Add 20 wt% PVA solution as a binder to the powder obtained in step 2, grind and granulate, and uniaxially dry press into a cylinder of 12 mm (diameter) × 6 mm (thickness) at 20 MPa;
[0048] Step 4: Place the green sample obtained in step 3 into a high-temperature sintering furnace, heat it to 100°C at a heating rate of 5°C / min, then heat it to 600°C at a heating rate of 10°C / min and keep it at that temperature for 4h, finally cool it to 500°C at a heating rate of 5°C / min and then cool it to room temperature with the furnace to obtain a green sample after debinding;
[0049] Step 5: The green sample after debinding in step 4 is placed in a high-temperature sintering furnace again, and the temperature is raised to 100°C at a rate of 5°C / min, and then raised to 1000°C at a rate of 10°C / min, and then raised to 1040-1080°C at a rate of 5°C / min for sintering, and kept at this temperature for 4 hours. After the end of the heat preservation, the temperature is lowered to 500°C at a rate of 5°C / min, and then cooled to room temperature with the furnace to obtain the silicate microwave dielectric material Li(Yb 0.25 Ho 0.25 Tm 0.25 Y 0.25 )SiO4;
[0050] The phase composition of the sample sintered at 1040-1080℃ is as follows Figure 3 As shown in the figure, Li(Yb 0.25 Ho 0.25 Tm 0.25 Y 0.25 )The phase composition of SiO4 is LiTmSiO4 phase and Y2SiO5 phase. Figure 4 It can be seen from the microwave dielectric properties of the sample at 1060℃, τ f =+31.6ppm / ℃, Q×f=4800GHz, ε r =8.8. The oxygen octahedron is distorted to 7.1×10 -4 τ of LiInSiO4 f The value is -50ppm / ℃; according to the multiphase composite material τ f The calculation formula of the value, τ f [Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 )SiO4]=
[0051] 0.8τ f [Li(Yb 0.25 Ho0.25 Tm 0.25 Y 0.25 )SiO4]+0.2τ f [LiInSiO4] = 0.8 × 31.6 + 0.2 × (-50) = 15.28 ppm / °C, which is much larger than the τ of the above-mentioned embodiment 1 at 1060°C. f This comparative example also proves that the addition of In element makes the material τ f Closer to zero.
[0052] It should be particularly noted that the present invention is not limited to the above-mentioned embodiments, and many changes in details are possible. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high entropy silicate microwave dielectric material that achieves temperature stability based on oxygen octahedral distortion regulation, characterized in that: The chemical composition of the material is: Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 )SiO4, the sintering temperature during preparation is 1060~1140℃.
2. The high entropy silicate microwave dielectric material for achieving temperature stability based on oxygen octahedral distortion regulation according to claim 1, characterized in that: The sintering temperature during preparation is 1060-1100°C.
3. The method for preparing a high entropy silicate microwave dielectric material based on oxygen octahedral distortion regulation to achieve temperature stability according to claim 1 or 2, characterized in that: The steps include: (1) Using Yb2O3, Ho2O3, Tm2O3, In2O3, Y2O3 and Li2CO3 as raw materials, according to Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 ) SiO4 stoichiometric ratio is weighed, and then the weighed raw materials are mixed and ball milled once, and the materials are dried to obtain a dried material; (2) The dried material obtained in step (1) is placed in an alumina crucible and compacted, and the temperature is raised to 1000° C. at a rate of 3 to 6° C. / min, and then kept at this temperature for 2 to 6 hours, and then cooled to room temperature with the furnace to obtain Li(Yb 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 )SiO4 calcined material; (3) Li(Yb) obtained in step (2) 0.2 Ho 0.2 Tm 0.2 In 0.2 Y 0.2 ) SiO4 pre-sintered material is placed in a ball mill, and subjected to secondary ball milling and mixing to obtain a slurry; (4) drying the slurry obtained in step (3) to constant weight, then granulating it and pressing it into a sample; (5) placing the sample obtained in step (4) in a high-temperature sintering furnace, heating the temperature to 400-600° C. at a heating rate of 3-6° C. / min and keeping the temperature for 2-6 h, and finally cooling the sample to room temperature in the furnace to obtain a debinding green sample; (6) placing the green sample obtained in step (5) in a high-temperature sintering furnace, heating the temperature to 1060-1140° C. at a heating rate of 3-6° C. / min, and keeping the temperature for 2-6 h, and finally cooling the furnace to room temperature to obtain a high entropy silicate microwave dielectric material with a resonant frequency temperature coefficient of near zero.
4. The method according to claim 3, characterized in that: In both step (1) and step (3), zirconium oxide balls are used as grinding balls and deionized water is used as ball milling medium.
5. The method according to claim 3, characterized in that: In step (4), 20 wt % PVA solution is added as a binder during granulation.
6. The method according to claim 3, characterized in that In step (4), the pressing pressure is 20 MPa, and the size of the pressed cylindrical sample is: diameter 12 mm×thickness 4-6 mm.
Citation Information
Patent Citations
Double-phase high-entropy silicate system microwave dielectric material with low sintering temperature and preparation method of double-phase high-entropy silicate system microwave dielectric material
CN118206364A
Olivine type lithium-containing silicon-based compact ceramic and preparation method thereof
CN119100772A
Functional barrier coating and related methods thereof
WO2020047278A1